IMPLEMENTASI TRI HITA KARANA DALAM PENGELOLAAN DAYA TARIK WISATA JATILUWIH, TABANAN - Dewa Ayu Diyah Sri Widari (UHN IGB Sugriwa Denpasar, 2024)
Based on the philosophical foundation of the designation of Subak as a World Cultural Heritage by UNESCO and the purpose of establishing the Jatiluwih Tourist Attraction Management Agency, the management of tourist attractions is expected to provide sustainable benefits based on the Tri Hita Karana concept. This study aims to examine the implementation of three aspects contained in the Tri Hita Karana concept in the sustainable management of Jatiluwih Tourist Attraction. This study used qualitative descriptive analysis method. Research instruments or tools used in the form of recording tools, cameras, notebooks, and interview guidelines. Data collection techniques used are observation, interviews and documentation. The results showed that Tri Hita Karana as the philosophical basis for the determination of Subak as a World Cultural Heritage needs to be maintained. Likewise, in the management of tourist attractions, the Tri Hita Karana philosophy needs to be implemented in order to provide sustainable benefits. The concept of Tri Hita Karana in the management of Jatiluwih Tourist Attraction from the aspects of parhyangan, pawongan, and palemahan has been implemented well, but there are several indicators that have not been implemented properly.